Twoblotch ponyfish Nuchequula blochii (Valenciennes, 1835) in the Sundarban Reserve Forest habitat of Bangladesh: Second record and establishment probability. Issue 3 (1st July 2021) - Hanif, Md. Abu; Hossen, Shaharior; Sharker, Md. Rajib; Siddik, Muhammad A. B.
Abstract: Climate changes and anthropogenic activities have paved the way for the dislocation of native species into areas located far away from their natural habitats. To this end, the Bay of Bengal and its adjacent coast have experienced the invasion of many alien species coming from different oceans, seas and bays around the world. Recently, a single specimen of the Twoblotch ponyfish ( Nuchequula blochii ) was captured. It had a total length of 69 mm and bodyweight 0.98 g. The specimen was caught at a depth of 18 m in the world's largest mangrove habitat, Sundarban, with a soft sandy bottom. Because the species N .  blochii was previously recorded for the first time in the water area of Bangladesh, the single captured species above was considered as the 'second record.' There are several potential factors responsible for the introduction of this species in the Bay of the Bengal coast, one being the similar habitat conditions available to them. Because this species was previously reported from the water area of Bangladesh and is still appearing now, there is a possibility that it may become established in the water area of Bangladesh.